Impact of Bullying on the Mental Health of Children and Adolescents: Mechanisms of Emergence and Consequences - Gura Андрій; Sodolevska Валерія (Psychosomatic Medicine and General Practice, 2024)
Relevance. Recently, numerous negative phenomena (conflict, aggression, cruelty) have been observed in interpersonal relationships among adolescents, often beginning in school. Behaviors related to violence among schoolchildren have been labeled as bullying, harassment, and abuse. In international psychology, such phenomena are referred to as "school bullying." Despite its undeniable significance, the issue of bullying in domestic psychological literature remains scarcely addressed and requires further investigation. Aim. The aim of this study is to analyze the scientific literature and research regarding the characteristics of bullying among children and adolescents and to assess its impact on both mental and physical health. Materials and methods. A qualitative and quantitative content analysis was conducted on both Ukrainian and English scientific literature addressing the consequences of bullying for adolescents. Searches were performed using the PubMed and Google Scholar databases, as well as the UNICEF Ukraine website. The primary objective was to investigate the impact of bullying on the mental health of adolescents. Articles focusing on the psychological and neurobiological consequences of bullying were included. Exclusion criteria were: other types of articles such as original research, books, commentaries, etc. The search for English-language articles was performed using the keywords “bullying” AND “mental health” AND “teenagers.” The initial search yielded 154 articles in PubMed and 353 in Google Scholar. After content analysis, articles not meeting the inclusion criteria were excluded, and 9 articles were included in the study. The search for Ukrainian-language articles was conducted using the keywords “булінг”, “психічне здоров’я”, “підлітки.” Inclusion criteria were: (1) the work contains at least one of the keywords; (2) the work is dedicated to the impact of bullying on the mental health of adolescents. The initial search in Ukrainian yielded 4090 articles in Google Scholar containing one or several of the keywords. After content analysis, articles that did not meet the inclusion criteria were excluded, and 8 articles were included in the study. The analysis focused on researchers’ perspectives regarding the nature of bullying and its impact on the mental health of adolescents. Conclusions. The problem of bullying among adolescents is becoming increasingly relevant on a global scale due to its extensive spread and serious social consequences. According to research, victims of bullying are at a higher risk of developing anxiety disorders, depression, post-traumatic stress disorder (PTSD), as well as experiencing reduced levels of social adaptation. Scientific investigations into this issue have been ongoing for several decades, especially regarding its medical and psychosocial consequences. Research confirms that bullying not only triggers short-term psychological stress but also leads to long-lasting changes in the brain that may affect emotional regulation and behavior in adulthood.